Efektivitas Pembelajaran Kooperatif dengan Metode Lingkari Aku dalam Meningkatkan Pemahaman Siswa SD (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
This outreach program evaluates the efficacy of the Lingkari Aku cooperative learning model in enhancing conceptual mathematical grasp among elementary students. Carried out at SD Negeri 054945 Dogang during the 2023/2024 odd semester, this study employed a qualitative case study methodology. The target participants were students engaged in integer operation topics. Data acquisition involved systematic observation, assessment tests, and documentation. The findings demonstrate that the Lingkari Aku method markedly bolstered student engagement, stimulated proactive group dialogue, and refined their grasp of integer concepts. Beyond academic gains, the approach fostered essential social competencies, such as teamwork, interpersonal communication, and accountability. Although high student excitement necessitated rigorous classroom management, the method successfully established a dynamic and pleasurable mathematical learning atmosphere. Consequently, this model is endorsed as a viable pedagogical alternative for elementary mathematics, especially within the framework of educational community service initiatives.